Preparation and characterization of ZnO/graphene/graphene oxide/multi-walled carbon nanotube composite aerogels - Shen, Yang; Yuan, Zhihao; Cheng, Fengjiao; Cui, Zhen; Ma, Deming; Bai, Yueyue; Zhao, Shuqing; Deng, Jieyao; Li, Enling (Frontiers in Chemistry, 2022)
ZnO/Graphene (G)/Graphene Oxide (GO)/Multi-walled Carbon Nanotube (MCNT) composite aerogels with a three-dimensional porous structure were prepared by the sol-gel method under average temperature and alkaline conditions, combined with freeze-drying process and heat treatment process. The photocatalytic degradation of Rhodamine B (RhB) was mainly studied. The scanning electron microscope (SEM) test results showed that the morphology uniformity of the ZnO/G/GO/MCNT composite aerogel was significantly enhanced, which effectively solving the agglomeration problem of MCNT and ZnO. The photocatalytic degradation test results of RhB show that due to the synergistic effect of physical adsorption and photocatalytic degradation, the total degradation efficiency of RhB by ZnO/G/GO/MCNT could reach 86.8%, which is 3.3 times higher than that of ZnO. In addition, the synergistic effect of ZnO and G effectively hinders the recombination of photo-generated electron-hole pairs and enhances photocatalytic activity. The ZnO/G/GO/MCNT composite aerogel can be applied in the visible light catalytic degradation of water pollution.